Empowering Fashion MSMEs: The Role of Intellectual Capital and Sharia Financial Technology in Enhancing Adaptability and Competitive Advantage - Burhany, Dian Imanina; Aini, Nurfina; Sumiyati; Nurniah (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to investigate the impact of intellectual capital and Sharia financial technology (fintech) on adaptability and competitive advantage. The research is conducted using a quantitative approach, with purposive and convenience sampling technique, targeting MSME fashion businesses in two Indonesian cities (Bandung and Cimahi), and two regencies (Bandung and West Bandung Regency), that have been operating for more than a year and use Sharia banking services in business management. Data analysis techniques used Partial Least Squares and utilized the Smart PLS 3.0 application. The research findings indicate that intellectual capital does not influence adaptability, while Sharia fintech has a positive along with significant impact on adaptability. Conversely, intellectual capital significantly drives the achievement of competitive advantage, while Sharia fintech does not have a great effect on competitive advantage. Adaptability is proved have a crucial role in strengthening the competitive advantage of MSMEs. Therefore, to achieve sustainable competitive advantage, the utilization of Sharia fintech must be accompanied by an enhancement of organizational adaptability. The result of this study emphasize the urgent of strengthening intellectual capital (human capital, structural capital, and relational capital) and adaptability in facing the dynamic changes in the business environment to empowering fashion MSMEs.